Systemic abnormalities of psoriatic patients: a retrospective study - Yin L; Xu JL; Hu YY; Johnston A; Yin ZQ (Dove Medical Press, 2016)
Li Yin,1,* Jia-Li Xu,2,* Ying-Ying Hu,1 Andrew Johnston,3 Zhi-Qiang Yin,1 1Department of Dermatology, 2Department of Oncology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 3Department of Dermatology, University of Michigan, Ann Arbor, MI, USA *These authors contributed equally to this work Background: Psoriasis is a chronic immune-mediated inflammatory disease related to the metabolic syndrome, cardiovascular disease, and other comorbidities. However, so far there has been no specific research concerning systemic abnormalities in psoriatic patients. Objective: A retrospective study was conducted focusing on the detailed systemic abnormalities in psoriatic patients. Methods: Psoriatic inpatients data was collected from July 2009 to September 2015. The inclusion criteria were first-time hospitalization and without administration of systemic drug therapy or exposure to phototherapy for psoriasis for at least 1 month. Detailed systemic indexes were mainly evaluated. Results: The abnormality rates of blood routine examination, urine examination, blood biochemical examination and chest X-ray of 43 psoriatic patients were significantly higher than those of 44 non-psoriasis controls, and psoriasis patients significantly had higher absolute values of leukocytes and neutrophils, and significantly lower values of lymphocytes. Compared with psoriasis vulgaris, erythrodermic psoriasis had significantly higher abnormality rates of blood biochemical examination and serum electrolyte analysis. Erythrodermic psoriasis had significantly higher absolute values of blood leukocytes, neutrophils, and lower serum calcium compared with those of psoriasis vulgaris. The neutrophil-to-lymphocyte ratio of controls was significantly lower than that of psoriatic patients, and neutrophil-to-lymphocyte ratio of erythrodermic psoriasis was significantly higher in comparison with psoriasis vulgaris. Conclusion: This study is the first report in relation to a detailed assessment of systemic abnormalities in psoriatic patients prior to onset of systemic treatment. The systemic condition of psoriatic patients should be observed by clinicians before systemic therapy. Keywords: psoriasis, skin, inflammation, treatment